The Influence of Product and Facility Diversity on Consumer Loyalty at Yuank Canteen, Bima City - Fatuniah; Sulhaini (Future Techno-Science, 2025)
Economic progress has driven rapid growth in the business sector, including food businesses such as canteens and restaurants. Increasingly tight competition requires business actors to increase competitive advantages, one of which is through product diversity and service facilities that can increase customer satisfaction and loyalty. This study aims to examine the effect of product and facility diversity on customer loyalty with a quantitative approach. The location of the study was Yuank Canteen in Bima City, with a sample of 100 respondents selected using purposive sampling techniques. The research instruments were tested for validity and reliability, and analyzed using multiple linear regression accompanied by t-test, F-test, and coefficient of determination. The results showed that product and facility diversity partially and simultaneously had a significant effect on customer loyalty. This finding underlines the importance of product innovation and the provision of adequate facilities as a strategy to build customer loyalty. It is recommended that Yuank Canteen increase promotions through social media as an effort to expand market reach and build closer relationships with consumers.